1980
DOI: 10.3109/01913128009141439
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Carcinomas of the Esophagus

Abstract: Of a total of 928 primary esophageal cancers, 16 cases of "undifferentiated" esophageal carcinoma were isolated. The topographic and age distributions as well as the clinical presentation and evolution of these tumors were basically similar to those of the usual esophageal squamous carcinoma. By light microscopy, the tumors were comprised exclusively or predominantly of small, round-to-fusiform cells. The cytoplasm appeared scanty and the nuclei were comparatively large and hyperchromatic. Mitotic activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…NEC, though representing only 1% of esophageal malignancies, has been reported more often in the esophagus than in any other extrapulmonary site . In contrast, lower‐grade endocrine neoplasms in the esophagus (carcinoid tumors and atypical carcinoid tumors) are too uncommon to characterize clinically .…”
Section: Primary Nonepithelial and Specialized Epithelial Tumors Of Ementioning
confidence: 99%
“…NEC, though representing only 1% of esophageal malignancies, has been reported more often in the esophagus than in any other extrapulmonary site . In contrast, lower‐grade endocrine neoplasms in the esophagus (carcinoid tumors and atypical carcinoid tumors) are too uncommon to characterize clinically .…”
Section: Primary Nonepithelial and Specialized Epithelial Tumors Of Ementioning
confidence: 99%
“…Sasajima et al [3] demonstrated one case of esophageal carcinoma showing multiple differentiation into oat cell carcinoma, adenoid cystic carcinoma, adenocarcinoma, and squamous cell carcinoma. Reyes et al [4] identified that small cell carcinoma coexisted with squamous cell carcinoma in 4/16 cases. Reid et al [5] showed a case of combination of small cell carcinoma and squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapulmonary malignant neoplasms composed largely or entirely of small neoplastic cells with a markedly hyperchromatic nucleus and scanty cytoplasm have been described as small cell carcinoma [4,7,9], neuroendocrine carcinoma [13,14], anaplastic carcinoma [15], or small cell epidermoid carcinoma [16]. Unlike lung cancer, extrapulmonary neoplasms of this type are uncommon but have been reported in a variety of other organs [4, 7-9, 13, 15].…”
Section: Discussionmentioning
confidence: 99%